2023
DOI: 10.18006/2023.11(1).75.80
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Potential of Chloranthus erectus (Chloranthaceae) from various solvents extract

Abstract: Chloranthus erectus is a herbaceous plant that has been used as a medicinal plant in several regions such as China and Southeast Asia. Although it possesses valuable medicinal properties, till now there is not much research has been carried out on the medicinal properties of this plant and the knowledge of this plant is limited among the research fertility. Therefore, this study aimed to identify the phytochemicals, total phenolic content (TPC), and antioxidant activity of leaf and twig of C. erectus in variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The highest TPC was recorded for the ethanol extract at 0.35 mg GAE/g sample. In a previous study, the highest TPC was recorded for a methanolic extract of the leaf sample at 9.64 ± 0.15 µg GAE/g dry weight [20]. The total flavonoid content was found to be highest in the ethanol extract (15.46 µgRE/g).…”
Section: Total Phenolic Compound and Total Flavonoid Contentmentioning
confidence: 77%
See 2 more Smart Citations
“…The highest TPC was recorded for the ethanol extract at 0.35 mg GAE/g sample. In a previous study, the highest TPC was recorded for a methanolic extract of the leaf sample at 9.64 ± 0.15 µg GAE/g dry weight [20]. The total flavonoid content was found to be highest in the ethanol extract (15.46 µgRE/g).…”
Section: Total Phenolic Compound and Total Flavonoid Contentmentioning
confidence: 77%
“…In the case of Chloranthus erectus, the IC 50 value for the DPPH scavenging activity was 6.98 ± 0.93 mg/mL in the methanol extract and 4.00 ± 1.78 mg/mL in another study, where the highest antioxidant activity was observed in the methanol extract of both the leaves (88.36 ± 0.24%) and twigs (91.25 ± 0.10%) [20]. Furthermore, the IC 50 values for ABTS radical scavenging activity in the ethanol extract were 45.18 mg/mL.…”
Section: Antioxidant Capacitymentioning
confidence: 80%
See 1 more Smart Citation